FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA INDUSTRI PERTAMBANGAN DI BURSA EFEK INDONESIA - MEIRISKA FEBRIANTI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2012)
This study aims to determine the factors that affect the value of the company in the mining industry in Indonesia Stock Exchange. These factors, namely, funding decisions, investment decisions and dividend policy. However, in further studies, the factors that are used only on funding decisions, ie to test the theories of capital structure and see its effect on firm value. The population in this study is a mining company listed on the Indonesia Stock Exchange for the period 2003 till 2007 with a total sample as many as 15 companies. The data is then analyzed using multiple regression analysis. The results showed that the growth opportunities, firm size and the ratio of total debt to equity ratio have impact on firm value. While the factors asset structure, profitability, liquidity and debt to total assets ratio have no effect on firm value.